Persepsi Gen Z terhadap Penggunaan Social Media Marketing sebagai Media Komunikasi dalam Proses Keputusan Pembelian Kopi Kenangan - Olivia Efendi; Giyana Giyana (Jurnal Manajemen dan Ekonomi Kreatif, 2025)
The advancement of digital technology has transformed marketing landscapes, with social media emerging as a strategic platform to engage consumers. Generation Z, born between 1997 and 2012, exhibits a strong connection to social media and is influenced by digital content during their purchasing decisions. This study investigates Generation Z's perception of social media marketing as a communication medium in the decision-making process for purchasing Kopi Kenangan products. Using a qualitative literature study method, data were gathered from scholarly articles, journals, and related documents published between 2020 and 2024. The findings highlight that interactive and personalized social media marketing strategies significantly impact Generation Z's perception and purchasing decisions. This research contributes to the understanding of effective digital marketing strategies for local coffee brands, providing insights into how Generation Z responds to and engages with such efforts.